Circadian gating of cell division in cyanobacteria growing with average doubling times of less than 24 hours. - Mori, T (1996)
To ascertain whether the circadian oscillator in the prokaryotic cyanobacterium Synechococcus PCC 7942 regulates the timing of cell division in rapidly growing cultures, we measured the rate of cell division, DNA content, cell size, and gene expression (monitored by luminescence of the PpsbAI::luxAB reporter) in cultures that were continuously diluted to maintain an approximately equal cell density. We found that populations dividing at rates as rapid as once per 10 h manifest circadian gating of cell division, since phases in which cell division slows or stops recur with a circadian periodicity. The data clearly show that Synechococcus cells growing with doubling times that are considerably faster than once per 24 h nonetheless express robust circadian rhythms of cell division and gene expression. Apparently Synechococcus cells are able to simultaneously sustain two timing circuits that express significantly different periods.